The full mitochondrial genome sequence of Raillietina tetragona from chicken (Cestoda: Davaineidae). (1st November 2016) - Liang, Jian-Ying; Lin, Rui-Qing
Abstract: In the present study, the complete mitochondrial DNA (mtDNA) sequence of Raillietina tetragona was sequenced and its gene contents and genome organizations was compared with that of other tapeworm. The complete mt genome sequence of R. tetragona is 14, 444 bp in length. It contains 12 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and two non-coding region. All genes are transcribed in the same direction and have a nucleotide composition high in A and T. The contents of A + T of the complete mt genome are 71.4% for R. tetragona . The R. tetragona mt genome sequence provides novel mtDNA marker for studying the molecular epidemiology and population genetics of Raillietina and has implications for the molecular diagnosis of chicken cestodosis caused by Raillietina .